0347 Sleep health education and a personalized smartphone application improve sleep and productivity and reduce healthcare utilization among employees: Results of a randomized clinical trial. (25th May 2022) - Robbins, Rebecca; Weaver, Matthew; Quan, Stuart; Sullivan, Jason; Cohen-Zion, Mairav; Glasner, Laura; Czeisler, Charles; Barger, Laura
Abstract: Introduction: Sleep deficiency and undiagnosed or untreated sleep disorders are pervasive among employed adults, yet are often ignored in the context of workplace health promotion. Smartphone applications (apps) are a promising, scalable approach to improving sleep among employees. We evaluated an online sleep education program followed by access to a mobile sleep training program, the dayzz app, that promotes healthy sleep, sleep disorders awareness and intervention. Methods: In a sample of daytime employees affiliated with a large healthcare organization, we evaluated the intervention (sleep education at baseline plus access to the personalized app for up to 9 months) in a parallel group, randomized controlled trial. Participants were randomly assigned to either the experimental condition that received the intervention in months 1 through 9 or the control group that was assigned to receive the intervention in month 10. In a prespecified data analysis plan, the experimental and control groups were compared in months 1 through 9; no outcome data was collected thereafter. We collected data on employee sleep, workplace outcomes, and healthcare utilization, monthly throughout the study. Results: The final cohort was comprised of 794 participants assigned to the experimental and 561 to the control condition. Those assigned to the experimental condition were more likely to maintain consistent sleep schedules (OR:1.40;95%CI:1.12-1.75) and less likely to experience fatigue and sleepiness (OR:1.30;95%CI:1.08-1.57). At the 9-month follow-up assessment, the experimental group reported significantly longer sleep duration than the control group on work (experimental: 7.20hrs; control: 6.99hrs, p=0.01) and free (experimental: 8.26hrs; control: 8.04hrs, p=0.03) nights. The odds of poor sleep quality at follow-up were lower in the experimental condition (OR:0.79, 95%CI:0.63-0.98) as compared to control. Mean total dollars lost due to presenteeism was less among experimental compared to control participants (p=0.0001), corresponding to an average of 274 saved per person per month. Finally, participants in the experimental group were less likely to report mental health visits (p=0.01) and had a lower rate of overall healthcare utilization (p=0.03), compared to the control group. Conclusion: Results from this randomized clinical trial demonstrate that a digital workplace sleep wellness program can be beneficial to both employees and employers, by improving employee sleep and fatigue, increasing work productivity, and reducing direct healthcare costs. Support (If Any): This study was funded by dayzz Live Well Ltd.